Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan - M. Taqiudin Fahri; A. Yahya Surya Winata (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
Competition in coffee shop business today is very tight. Coffee is a favorite drinks of Indonesian people, especially collage students. Based on this, several coffee shop are required to have their own characteristics in order to attract customers. However, the characteristics without being supported by the quality of sevice in serving these drinks also need to be considered. This study aims to determine the effect of sevice quality on customer satisfaction by conducting a study on customers of Warung Wayang. The variables used in this study are tangible, reliability, responsiveness, assurance, empathy, and customer satisfaction. Testing data analysis in this study was conducted using the IBM SPSS Statistics 22 For Windows program. Simultaneously, the variables of tangible, reliability, responsiveness, assurance, and empathy have an effect on customer satisfaction.